In justified anger1. Issue 2 (July 2020) - O'Keefe, Phil; O'Keefe, Paul
There were certain assumptions underlying the (early) government response to the pandemic in Britain. The first one was to try and preserve capital accumulation for the very rich by making the rest of the population suffer, a population that had experienced austerity for years. The second assumption signifying thinly disguised racism was to deny that what originated in China had any relevance to the United Kingdom. A corollary of this was: if other countries wished to shut down, the United Kingdom would reap the benefits. These assumptions which led to relative inactivity in the early stage of the pandemic prompt us to ask: what human value system puts the preservation of the capitalist market economy above saving human lives?